How to make building renovation work for low-income renters: Preferences for distributional principles and procedural options in Austria. (December 2021) - Seebauer, Sebastian
Highlights: General justice terms spelt out to those who may be most affected by injustices. Survey operationalisation of distributional principles and procedural options. Acknowledges heterogeneous capabilities of vulnerable groups. Shows interrelations and common drivers of distributional and procedural justice. Abstract: Widespread thermal refurbishment of existing buildings is essential for mitigating carbon emissions and energy poverty. Retrofitting for better energy efficiency in low-income rental housing comes up against the tenant-landlord dilemma, however; for renovation to be accepted by residents, rules for cost sharing and fair implementation are required. The present study employs structural equation modelling to analyse distributional and procedural preferences in a survey sample of 942 social welfare recipients in Austria. The distributional principles of polluter-pays and energy bill neutrality are preferred for allocating renovation costs. Equal-pay, ability-to-pay, and paying extra instalments to finance the renovation are only accepted for buildings in high need of renovation. Low-income renters welcome a wide range of procedural options, in particular, providing transparent and comprehensive information on the planned renovation and mitigating inconvenience during the construction phase. Psychological and relational capabilities play into these preferences: households holding pro-environmental attitudes favour polluter-pays to prevent free-riders. A frugal mindset, trust in the landlord and renter concerns make low-income renters endorse ability-to-pay to avoid being displaced to lower-grade dwellings on a discriminating housing market. The results suggest that distributional principles need not stand alone but could be combined. For instance, allocating the majority of renovation costs by polluter-pays, but a smaller share by ability-to-pay, may cushion disproportionate impacts on less affluent residents. Energy counselling could empower low-income renters to manage personal energy and renovation costs, and to build literacy about renovation benefits and legal claims to encourage their landlord to renovate.